2022
DOI: 10.1097/sap.0000000000003146
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Chronic Pain in Postmastectomy Patients

Abstract: BackgroundAfter breast surgery with or without immediate reconstruction, chronic pain can be a major problem for patients. However, few studies have examined the details of the sites of long-lasting postoperative pain. In this study, we specified the postoperative pain location after breast surgery, including reconstruction, to find ways to improve surgical procedures or provide effective pain relief.MethodsThe subjects were 205 Japanese women undergoing mastectomy or breast reconstruction with a tissue expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In alloplastic reconstruction, Wang et al 53 reported rates of chronic pain in the breast, chest wall, axilla, and arm of 30.2%, 21.4%, 16.4%, and 6.9%, respectively. Among breast surgery options, implant-based reconstruction results in less severe pain in the medial breast ( P = 0.006), upper breast ( P = 0.006), upper medial breast ( P < 0.001), and abdomen ( P < 0.001) at POY 1, whereas infraclavicular pain was specifically observed in implant-based reconstruction ( P = 0.025) 45 . Pain in the infraclavicular region may be due to direct pressure on the brachial plexus in this area following migration of implants 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alloplastic reconstruction, Wang et al 53 reported rates of chronic pain in the breast, chest wall, axilla, and arm of 30.2%, 21.4%, 16.4%, and 6.9%, respectively. Among breast surgery options, implant-based reconstruction results in less severe pain in the medial breast ( P = 0.006), upper breast ( P = 0.006), upper medial breast ( P < 0.001), and abdomen ( P < 0.001) at POY 1, whereas infraclavicular pain was specifically observed in implant-based reconstruction ( P = 0.025) 45 . Pain in the infraclavicular region may be due to direct pressure on the brachial plexus in this area following migration of implants 44 …”
Section: Discussionmentioning
confidence: 99%
“…43,44 Honkanen et al 36 compared the location of chronic pain following implant-based and autologous reconstruction and found no difference in pain between the reconstruction types. However, in similar but larger cohort studies, Shiraishi et al 45,46 found that patients who received autologous reconstruction reported more abdominal pain at postoperative year (POY) 1 (P < 0.001) and POY 5 (P = 0.04), and more upper medial breast pain at POY 5 (P = 0.01) compared to patients treated with mastectomy only. Abdominal pain can be caused by donor harvest, whereas pain in the upper medial breast may be due to rib removal 47 and damage to intercostal nerves in the search for internal mammary vessels.…”
Section: Location Of Chronic Painmentioning
confidence: 95%